Palaeomagnetism and tectonics of Middle America and adjacent regions. Part 2 - Urrutia Fucugauchi, Jaime (Geofísica Internacional, 1983)
This issue presents the second part of a special collection of papers concerned with recent palaeomagnetic and tectonic investigations of Mexico. It contains a total of four papers, written by four authors from four different institutions. Three papers present palaeomagnetic results of relevance to the tectonic evolution of Mexico during the Cretaceous and Tertiary, whereas the other paper discuss the tectonic evolution and setting of Mexico, following a regional geologic approach.